Analisis Kualitas Pelayanan Front Office terhadap Kepuasan Wisatawan di Hotel Inna Heritage Denpasar Bali - Sudharma Yadnya, Putu Agus Wisnu; Jamin Ariana, Ni Nyoman; Sutaguna, I Nyoman Tri (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
In the world of hospitality, many service departments, especially the front office, offer hotel facilities. The front office department is the front part of the hotel which is seen by tourists as the first impression of a hotel service when tourists make a reservation by phone or when checking in directly at the hotel, for that reason the readiness, readiness, accuracy and ability of the employees at the front office The department in carrying out its duties and responsibilities plays an important role in giving positive and negative impressions to guests before these guests get services and other experiences when they come to stay or just visit a hotel. Hotel Inna Bali Heritage, one of the three-star hotels in the Denpasar area, Bali. Hotel Inna Bali Heritage which also has its own organizational structure to run the hotel optimization is growing. Inna Bali Heritage Hotel, located in the center of Denpasar City. The purpose of this research is to determine the quality of services in Inna heritage Hotel Denpasar on the satisfaction of tourists who stay. The type of data used in this study is qualitative data in the form of an overview of the hotel, hotel organizational structure and structured interviews. Meanwhile, the quantitative data used is the result of a questionnaire that has been previously distributed to respondents. The technique of determining the respondents used is accidental sampling in which the respondents are determined randomly and found by chance with the researcher. The data analysis technique used is descriptive quantitative with attitude scale calculations, and data analysis using Cartesian diagrams to determine the level of importance of each proposed indicator. The results of this study indicate that several variables in the B quadrant are important indicators and need to be maintained. The role of bellboys who get good ratings from tourists needs to be maintained, besides that the front desk agent has an important role in tourist satisfaction with the services provided at the front office department. Good understanding of English, as well as the completeness of communication equipment for front office department employees that are good and need to be maintained in order to be able to provide quality services in accordance with tourist expectations. Key Word : Service Quality, Front Office Department, Cartesian Diagram.